Dual function of CALCOCO2/NDP52 during xenophagy - Verlhac, Pauline (Autophagy, 2015)
During xenophagy, pathogens are selectively targeted by autophagy receptors to the autophagy machinery for their subsequent degradation. In infected cells, the autophagy receptor CALCOCO2/NDP52 targets Salmonella Typhimurium to the phagophore membrane by concomitantly interacting with LC3C and binding to ubiquitinated cytosolic bacteria or to LGALS8/GALECTIN 8 adsorbed on damaged vacuoles that contain bacteria. We recently reported that in addition, CALCOCO2 is also necessary for the maturation step of Salmonella Typhimurium-containing autophagosomes. Interestingly, the role of CALCOCO2 in maturation is independent of its role in targeting, as these functions rely on distinct binding domains and protein partners. Indeed, to mediate autophagosome maturation CALCOCO2 binds on the one hand to LC3A, LC3B, or GABARAPL2, and on the other hand to MYO6/MYOSIN VI, whereas the interaction with LC3C is dispensable. Therefore, the autophagy receptor CALCOCO2 plays a dual function during xenophagy first by targeting bacteria to nascent autophagosomes and then by promoting autophagosome maturation in order to destroy bacteria.